Transitional cell carcinoma of urinary bladder with cervical lymph node metastasis: a case report and review of literature - V., Ramya; J., Sahayaraj (International Journal of Advances in Medicine, 2019)
Bladder cancer usually spreads via the lymphatic and hematogenous routes, the common sites of metastases of urinary bladder cancers being the regional lymph nodes, liver, lung, bone, peritoneum, pleura, kidney, adrenal gland and intestines. Metastasis to non-regional lymph nodes especially cervical lymph nodes is extremely rare presentation. Metastasis to head and neck region is associated with poor prognosis and low survival rate. Here-in we report a case of cervical lymph node metastasis in patient with muscle invasive bladder cancer.